PENGARUH SHARIA MARKETING MIX TERHADAP KEPERCAYAAN PELANGGAN DAN KEPUTUSAN PEMBELIAN PADA ONLINE SHOP TIWS.ID - Anah, Isti (UIN Sayyid Ali Rahmatullah Tulungagung, 2018)
Abstract. Online shop development or online shop through social media has already existed in Indonesia, moreever it is being really potential things and give is easier to seller and buyer even online shop is being more popular than before and it causes the competition highly (begin), but beside that, the facility has been making the shop site badly or it has been making deception site by anyone who didn’t responsibly. Therefore, the facility has to influence on directness of online shop and trusting costumer then purchase decision. So, it needs inapplying the strateghy for making /getting customer’s trusting and the costumer decide to do purchas. One of its is sharia marketing mix 9P (product, price, place, promotion, peolpe, physical evidance, process, promise, and patience). Based on reason, the research is to investigate the effect of sharia marketing mix to customer’s trusting and purchase decision on online shop Tiws.id. quantitative method is used in conducting the research. To collect the data, questionaire, technique are used to conduct the research meanwhile, analysis regresi linier with SPSS 16’s program are used in analyzig the data. The data analysis showed that the strateghy sharia marketing mix to Tiws.id online shop has an alternative hypotesis to customer’s trusting and purchase decision. It means that,in applying sharia marketing mix better,it make customer trusting ang purchase decision to Tiws.id online shop as good as possible. Keywords: Sharia Marketing Mix, Customer Trusting, Purchase Decision and Online Shop